Impact of lymph node occult metastases in stage I non-small cell lung cancer (NSCLC): what is the evidence? - Marulli, Giuseppe; Mammana, Marco; Rea, Federico (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
With the improvement in imaging techniques, and the development of screening protocols for lung cancer, a growing number of patients are expected to be diagnosed with early stage non-small cell lung cancer (NSCLC). The landmark National Lung Screening Trial, gives us a hint: out of 1,060 new cases of lung cancer diagnosed in patients undergoing annual low-dose chest computed tomography screening and 941 cases diagnosed with chest radiography, the proportion of stage I lung cancers was respectively 50% and 31% in the two groups (1).